2011
DOI: 10.9734/acsj/2011/214
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde, Ketone and Methane Emissions from Motor Vehicle Exhaust: A Critical Review

Abstract: Recent data indicate that, in many countries, mobile sources are responsible for the largest portion of emissions of aldehydes, ketones and certain other air toxic pollutants. These air toxic pollutants along with methane are either carcinogenic or pose significant human health threat. These pollutants also add to global warming in a substantial way. This paper gives an overview of their properties, basic chemistry and conditions of formation in internal combustion engines. Again worldwide many countries are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 41 publications
0
13
0
3
Order By: Relevance
“…This can be disregarded in this work since the 580 fuels do not contain nitrogen species in their composition. Table 1 [17,19,25,26,28,35,37,39]. Q7 800…”
Section: Introductionmentioning
confidence: 99%
“…This can be disregarded in this work since the 580 fuels do not contain nitrogen species in their composition. Table 1 [17,19,25,26,28,35,37,39]. Q7 800…”
Section: Introductionmentioning
confidence: 99%
“…Aldehyde vapors effects on human health include irritation of eye, throat, nose, asthma, pulmonary function. Thresholds for sensory irritation determined by controlled exposure studies, are reported as 0.6-1.2 mg/m 3 [0.5-1.0 ppm] (formaldehyde) and 90 mg/m 3 [50 ppm] (acetaldehyde) [53]. These levels are substantially higher than the generally reported ambient air concentrations of these vapors.…”
Section: Measurement Of Exhaust Emissionsmentioning
confidence: 97%
“…These aldehydes are carcinogenic in nature and once they are inhaled, cause severe headache and vomiting sensation [53]. Aldehyde vapors effects on human health include irritation of eye, throat, nose, asthma, pulmonary function.…”
Section: Measurement Of Exhaust Emissionsmentioning
confidence: 99%
“…Due to higher viscosity of biodiesel and Wintron Synergy, poor spray characteristics may lead to longer ignition delay causing higher NO x emissions. Although the share of NO 2 in total NO x in spark-ignition engines is negligibly small, it could be as high as 10-30% in diesel engines [38]. NO formed in the flame zone can be rapidly converted to NO 2 with reactions such as;…”
Section: No X Emissionsmentioning
confidence: 99%